The Penefit of Salience: Salient Accented, but Not Unaccented Words Reveal Accent Adaptation Effects - Grohe, Ann-Kathrin; Weber, Andrea (Frontiers in Psychology, 2016)
In two eye-tracking experiments, the effects of salience in accent training and speech accentedness on spoken-word recognition were investigated. Salience was expected to increase a stimulus’ prominence and therefore promote learning. A training-test paradigm was used on native German participants utilizing an artificial German accent. Salience was elicited by two different criteria: production and listening training as a subjective criterion and accented (Experiment 1) and canonical test words (Experiment 2) as an objective criterion. During training in Experiment 1, participants either read single German words out loud and deliberately devoiced initial voiced stop consonants (e.g., Balken – ‘beam’ pronounced as *Palken), or they listened to pre-recorded words with the same accent. In a subsequent eye-tracking experiment, looks to auditorily presented target words with the accent were analyzed. Participants from both training conditions fixated accented target words more often than a control group without training. Training was identical in Experiment 2, but during test, canonical German words that overlapped in onset with the accented words from training were presented as target words (e.g., Palme – ‘palm tree’ overlapped in onset with the training word *Palken) rather than accented words. This time, no training effect was observed; recognition of canonical word forms was not affected by having learned the accent. Therefore, accent learning was only visible when the accented test tokens in Experiment 1, which were not included in the test of Experiment 2, possessed sufficient salience based on the objective criterion “accent”. These effects were not modified by the subjective criterion of salience from the training modality.